If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + 6)(6x + 7) = 0 Reorder the terms: (6 + 6x)(6x + 7) = 0 Reorder the terms: (6 + 6x)(7 + 6x) = 0 Multiply (6 + 6x) * (7 + 6x) (6(7 + 6x) + 6x * (7 + 6x)) = 0 ((7 * 6 + 6x * 6) + 6x * (7 + 6x)) = 0 ((42 + 36x) + 6x * (7 + 6x)) = 0 (42 + 36x + (7 * 6x + 6x * 6x)) = 0 (42 + 36x + (42x + 36x2)) = 0 Combine like terms: 36x + 42x = 78x (42 + 78x + 36x2) = 0 Solving 42 + 78x + 36x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '6'. 6(7 + 13x + 6x2) = 0 Factor a trinomial. 6((7 + 6x)(1 + x)) = 0 Ignore the factor 6.Subproblem 1
Set the factor '(7 + 6x)' equal to zero and attempt to solve: Simplifying 7 + 6x = 0 Solving 7 + 6x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 6x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 6x = 0 + -7 6x = 0 + -7 Combine like terms: 0 + -7 = -7 6x = -7 Divide each side by '6'. x = -1.166666667 Simplifying x = -1.166666667Subproblem 2
Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Simplifying x = -1Solution
x = {-1.166666667, -1}
| (5r+4)(5r-4)= | | 9(0.75+0.25y)-2y=10 | | 9(0.75+0.25)-2y=10 | | 0=0.002037t^2+0.0170086t-0.06426 | | 2y+7=4 | | 21x^3-14x^2+15x-10=0 | | 5x+6=2x+42 | | 4.6x+3.4x=-24 | | 4x+5=3x+10 | | 7.5x-3.9=11.1 | | (3x)-(1)=-7 | | 9+6(x-7)=9-4(x-6) | | 5(x-4)=-10 | | 8m^2=-56m | | m^3+3m^2-4m-12=0 | | 5.8X-5.4=3.6X+1.8 | | 2x^2-1x-11=0 | | 17-1y=y+5 | | 2x+2y=34 | | 20y^2+37y+8=0 | | 14-y=y+2 | | 4d^2+11d-3=0 | | 5x+6c-2=12 | | 3(6z-1)-3(z+7)=8(z+1) | | 15m=16 | | -(4y+1)-(-3y-7)=0 | | 4x*x-13x+7=0 | | 4x^2-7x-8=0 | | 2x+5x^2=12 | | -2-2x=1 | | 0=9x^2+6x-3 | | 21x=-147 |